Pendidikan Vokasional Teknik Konstruksi Gedung dalam Perspektif Kurikulum Merdeka di Indonesia: Quo Vadis? - Masykur Kimsan (MEDIA KONSTRUKSI, 2024)
Vocational education in building construction technology has rapidly advanced since the 2000s, driven by industry demands for a skilled and adaptable workforce capable of responding to the latest technological advancements. Technological shifts, globalization, and demographic changes have spurred innovation in curricula and teaching methods, with the “Kurikulum Merdeka” providing the necessary flexibility to align education with industry needs. However, challenges such as institutional readiness and access to technology must be addressed through collaboration between the government, educational institutions, and the industrial sector. The diversity in educational levels within vocational building construction programs can become a strength if effectively managed through appropriate curricula and teaching strategies. The disparity in human resource quality between urban and remote areas hampers the implementation of Kurikulum Merdeka, necessitating cooperation among the government, private sector, and communities to enhance human resource quality and educational infrastructure. Balancing pragmatism, which emphasizes practical skills, with idealism, which focuses on ethics, is crucial for producing graduates who are both job-ready and possess strong integrity. Educational challenges include academic dishonesty and rigid conversion of vocational practices into a 20-credit system, potentially diminishing educational quality and graduate preparedness. Flexible regulations and approaches such as project-based learning and competency-based assessments are essential to adapting curricula to industry and technological needs. Continuous monitoring and evaluation are key to ensuring the relevance of education in meeting labor market demands